This ain't Hell (But you can see it from here!) (Cimarron, New Mexico Cimarron Legend, 1992)
Advertisement on the cartoonist Berry McWilliams Book on Desert Storm.
Master List item # 67
File location is in the Raton File Cabinet
Keywords: McWilliams, Barry; Desert storm; Cimarron Art Gallery; Troopers; Book; Cartoonist; Humor; War; Pranks/Jokes; Cimarron, New Mexico